CT-Guided Placement of a Neuromonitoring Suite in Swine for Trauma and Resuscitation Research - Bonin, Janet; Abdou, Hossam; Edwards, Joseph; Patel, Neerav; Richmond, Michael; Elansary, Noha; Poe, Kelly; Morrison, Jonathan J (Journal of Endovascular Resuscitation and Trauma Management, 2021)
Background: In this manuscript, we aim to describe a standardized method for placement of a neuromonitoring suite into the brain of a porcine model using computed tomography (CT) guidance for use in trauma and resuscitation research. Methods: A baseline CT allowed for precise planning of the placement of the neuromonitoring suite including measurement of skull thickness at the location of the intended burr hole. After the burr hole was drilled, three neuromonitoring probes (pressure catheter, temperature probe, and laser doppler flow probe) were advanced into the brain parenchyma of the swine. A subsequent CT confirmed appropriate placement of the neuromonitoring suite. Results: Effective placement of the neuromonitoring suite was accomplished successfully and without complication in six Yorkshire swine. Mean duration of the procedure was 49.6±6.3 min. Representative data from one animal include the following presented as mean ± standard deviation: intracranial pressure of 10±0 mmHg, cerebral perfusion pressure of 61±1 mmHg, intracranial temperature of 34.8±0 °C, and brain perfusion of 704±13 relative perfusion units. Conclusions: This CT-guided method facilitates placement of a neuromonitoring suite in a safe and reliable manner. The use of a neuromonitoring suite using CT may offer valuable insight into cerebral perfusion in the context of endovascular resuscitation.